IMPLEMENTASI NON PERFORMANCE LOAN ANALYSIS PADA PT.BANK RAKYAT INDONESIA (Persero) Tbk - Safri, Hayanuddin (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2020)
Non Performance Loans are an indicator of the soundness of a commercial bank. Because the high NPL shows the inability of commercial banks in the appraisal process up to the disbursement of credit to debtors, on the other hand NPL also causes high cost of capital (cost of capital) which is reflected in the operational costs of the commercial bank concerned. With the high cost of capital, it will affect the net profit from the bank. Based on calculations to find the NPL ratio, it will produce a ratio value, which describes the conditions currently being experienced by banks regarding credit problems. In this regard, Bank Indonesia has determined a fair ratio of NPLs of 5% of its total loan portfolio. In this case, a bank with an NPL ratio below 5% is still considered normal in its credit activity. The smaller the NPL ratio, the lower the risk of bad credit in a bank and the better its credit activity performance is in line with the theory attached above. The NPL ratio value generated by PT Bank Rakyat Indonesia (Persero) Tbk from 2013 to 2017 shows the value; 1.27%; 1.26%; 1.17%; 0.05% and 1.10%. This means that the rating value achieved is 1, which is very healthy.